Hepatoprotective Effect and Chemical Assessment of a Selected Egyptian Chickpea Cultivar - Essam Abdelsattar; Reham Mekky; Mostafa Fayed; Mohamed El-Gindi; Azza abdelmonem; María del Mar Contreras; Antonio Segura-Carretero (Frontiers Media S.A., 2016)
Chickpea (Cicer arietinum) is a legume of the family Fabaceae, subfamily Faboideae. In Egypt, chickpea seeds are usually consumed at raw green and tender stage, or in the form of mature dry seeds. In our previous study, 'Giza 1' seeds exhibited stronger antioxidant activity and high total phenol content than those from other Egyptian cultivars. In order to assess the biological potential of 'Giza 1' seeds in vivo, the extraction procedure was reproduced here. The extract was standardized using liquid chromatography (LC) coupled to diode array detector (DAD) and tandem mass spectrometry (MS/MS) to evaluate their hepatoprotective effect on CCl4-induced hepatotoxicity in rats and acute toxicity. Administration of the extract to rats in doses up to 2 g/Kg) did not cause any mortalities or observable signs of toxicity. Further, the plant extract showed a strong hepatoprotective activity based on assessing serum alanine aminotranferase, aspartate aminotranferase, and alkaline phosphatase and levels of albumen, globulin, total protein, total cholesterol, high density lipoprotein, triglycerides, and low density lipoprotein. The antioxidative activity was evaluated by assessing hepatic catalase and superoxide dismutase activity as well as reduced glutathione, and malondialdehyde levels. Additionally, anti-inflammatory activity was observed as the extract significantly lowered the hepatic tumor necrosis factor α content. Histopathological examination of liver tissues indicated that the extract-treated animals showed almost normal hepatic architecture with fewer pathological changes. In conclusion, the current results suggest that the chickpea extract possesses an excellent safety profile with very low acute toxicity. Also, it exhibits a significant hepatoprotective effect against CCl4-induced liver injury in rats. This can be attributed, at least partly, to the antioxidant and anti-inflammatory activity of the isoflavones and phenolic acids content of the extract.